Kajian Struktur Baja Sebagai Alternatif Review Design Struktur Beton Bertulang (Studi Kasus Bangunan 2 Lantai Puskesmas 9 Nopember Banjarmasin) - Syaikhani, Ahmad (Nusantara Journal of Science and Technology, 2025)
Current building construction uses more concrete structures, not many of which use steel structures. One of the advantages of using steel is that steel work is faster with simpler steel structure installation support tools, so that it can save procurement costs and time. This study aims to plan the 2-Storey Building of the Puskesmas 9 November Banjarmasin which initially used a reinforced concrete structure into a steel structure. The research method used is to plan columns and beams in the form of steel using the SAP2000 application and earthquake loading according to SNI 1726:2019. Through the calculation of loading and application of structural loads in SAP2000, the value of the ultimate load (Pu) acting on the column and the ultimate moment (Mu) on the beam are obtained. The value of the ultimate load (Pu) will affect the amount of the factored nominal load (?Pn), because the factored nominal load (?Pn) must be greater than the ultimate load (Pu) so that the building structure is safe. However, if the nominal factored load (?Pn) is too large than the ultimate load (Pu), it will cause waste in the building structure (column). From the calculation results, the WF steel profile used is 200.200.10.16 fy = 240 MPa for change a 30x30 column 1st floor and 100.100.6.8 fy = 240 MPa for change a 15x30 at column 2nd floof. On the 1st floor beam measuring 20x30 using the WF steel profile 200.150.6.9 fy = 240 MPa and on the 20x30 beams on floors 2 using the WF steel profile 200.150.6.9 fy = 240 Mpa or fy=450 MPa.